Evaluación de la representación estudiantil en la universidad desde un enfoque de género: diseño de un cuestionario - Cáceres Reche, María Pilar; Lorenzo Delgado, Manuel; Sola Martínez, Tomás (Enseñanza & Teaching: Revista Interuniversitaria de Didáctica, 2009)
RESUMEN: En este artículo se describe el procedimiento realizado para el diseño de un cuestionario que pretende abordar el estudio de las percepciones del liderazgo estudiantil en función del género en la Universidad de Granada. Se recogen las principales aportaciones de los estudios previos, en los que se enmarca nuestra propuesta de investigación a través del cuestionario, partiendo de una de las investigaciones pioneras acerca del liderazgo estudiantil implementada en el 2005 por el Dr. Lorenzo Delgado y el Grupo de Investigación A.R.E.A. (Análisis de la Realidad Educativa Andaluza) y de otra, centrada en la presencia de la mujer en los cargos directivos en la Universidad de Granada desde el curso académico 1999 hasta 2005. ABSTRACT: In this paper we describe the process used to design a questionnaire in order to establish the study of student leadership perceptions according to gender at the University of Granada. We include the main contributions of previous studies on which our research proposal through a questionnaire is based. One of these is a pioneer research study about student leadership carried out in 2005 by Dr. Lorenzo Delgado and the Research Group A.E.R.A. (Andalusian Educational Reality Analysis) and the other is a study focused on the presence of women in higher management positions in the University of Granada from 1999 to 2005. The novelty of this research responds to the need to know the leadership profile that emerges from student representatives, as members elected and as voters, one of the topics forgotten in «university micro-politics» and through which we can analyse the role of gender stereotypes in order to understand the reasons why they were elected, the expectations to be developed, how leadership is practised (methods, techniques, etc.) and their self-assessment.